Micellization behavior of mixed surfactants in pure water and methanol-water mixed solvent media by density methods - Bhattarai, Ajaya; Pathak, Kavita; Dev, Bikash (BIBECHANA, 2015)
The properties of anionic-rich and cationic-rich mixtures of dodecyltrimethylammonium bromide (DTAB) and sodium dodecylsulfate (SDS) in pure water and methanol-water mixed solvent media were studied using density measurements at room temperature. The results showed that density increases with increasing concentration of surfactant mixture over the entire concentration range investigated in pure water and in the given mixed solvent media and which are found to decrease with an increase in the volume fraction of methanol in the solvent composition. The critical micelle concentration increases with the increase in volume fraction of methanol for both the anionic-rich (SDS-DTAB) and cationic-rich (DTAB-SDS) systems.BIBECHANA 13 (2016) 114-120